1995
DOI: 10.1111/j.1472-765x.1995.tb01029.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of immunomagnetic separation for the detection of salmonellas in raw chicken carcasses

Abstract: Immunomagnetic separation techniques were used in the isolation of salmonella from raw chicken carcasses. Improved isolation rates were achieved with increased specificity and decreased processing time, although several technical difficulties remain to be addressed. Immunomagnetic separation offers significant potential for improvement on existing microbiological systems for the isolation of salmonella.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 3 publications
0
8
1
Order By: Relevance
“…The technique, which employs magnetic beads, has been used since the 1970's when Norwegian scientists tried to apply magnetism for biological investigation. IMS has been used successfully by some authors to replace enrichment in selective media (Coleman, Chick, & Nye, 1995). Thus far, the IMS/qRT-PCR method has been used to concentrate the virus and minimize inhibitors from food.…”
Section: Discussionmentioning
confidence: 99%
“…The technique, which employs magnetic beads, has been used since the 1970's when Norwegian scientists tried to apply magnetism for biological investigation. IMS has been used successfully by some authors to replace enrichment in selective media (Coleman, Chick, & Nye, 1995). Thus far, the IMS/qRT-PCR method has been used to concentrate the virus and minimize inhibitors from food.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that immunomagnetic separation (IMS) techniques may offer an advantage in improving microbiological systems for the detection of salmonellae (Coleman et al 1995). However, problems of specificity still remained, with a variety of organisms, notably mucoid coliforms, Citrobacter freundzz, pseudomonads and Proteus spp.…”
Section: Introductionmentioning
confidence: 99%
“…1998). Improved isolation rates have been described when using IMS in the isolation of salmonellae from raw chicken carcasses (Coleman et al. 1995a), skimmed milk powder (Dziadkowiec et al.…”
Section: Discussionmentioning
confidence: 99%